Tripoli's militia cartel : how ill-conceived stabilisation blocks political progress, and risks renewed war - Lacher, Wolfram (2018)
Zusammenfassung: Since the establishment of the UN-backed Government of National Accord (GNA) in Tripoli, in March 2016, a handful of local militias have gradually brought much of the Libyan capital under their control. Although nominally loyal to the GNA, these armed groups today in fact dominate the government. They have grown into criminal networks straddling business, politics, and the administration. The pillaging of state funds - a hallmark of Libya’s political economy - now benefits a narrower group than at any previous point since the 2011 revolution. Actors excluded from this arrangement are building alliances to alter the balance of power in Tripoli by force. New security arrangements for the capital are urgently needed to avert renewed conflict and prepare the ground for a broader political settlement